Prisonser’s suicides in india – Constitutional and Civil liability (International Journal of Scientific Research and Management (IJSRM), 2015)
Suicides by persons in custody, whether pre-trial detainees or convicted prisoners,is a troublesome and recurrent issue for jails and prisons. While suicide is recognized as a critical problem within the jail environment, the issue of prison suicide has not received comparable attention The present paper deals with the constitutional position on suicides and also certain prevention methods for controlling suicides in prisons. The paper analyses constitutional position regarding suicides in prison and to look into various pronouncements of courts in this matter and try to derive some convincing and credible solutions and elucidations to the intrigue problem of suicide in prison along-with formulating a dependable and steadfast suicide prevention programme.